2020
DOI: 10.12659/ajcr.927154
|View full text |Cite
|
Sign up to set email alerts
|

A Patient with Asymptomatic SARS-CoV-2 Infection Who Presented 86 Days Later with COVID-19 Pneumonia Possibly Due to Reinfection with SARS-CoV-2

Abstract: Patient: Male, 57-year-old Final Diagnosis: COVID-19 pneumonia • reinfection Symptoms: Cough • fever Medication: — Clinical Procedure: — Specialty: Infectious Diseases Objective: Unusual clinical course Background: Coronavirus disease 2019 (COVID-19) has radically changed the world, and promising vaccine trials are currently underway. The immune responses in asymptomatic and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 12 publications
(15 reference statements)
0
24
0
Order By: Relevance
“…1) (References in Table 1: Abdallah et al, 2020[ 1 ]; AlFehaidi et al, 2020[ 2 ]; Amoozgar et al, 2020[ 5 ]; Bonifácio et. al., 2020[ 9 ]; Chan et al, 2020[ 10 ]; Duggan et al, 2021[ 13 ]; Fernandes Valente Takeda et al, 2020[ 14 ]; Hanif et al, 2020[ 17 ]; He et al, 2021[ 18 ]; Lafaie et al, 2020[ 20 ]; Lancman et al, 2020[ 22 ]; Mulder et al, 2020[ 24 ]; Nachmias et al, 2020[ 25 ]; Selvaraj et al, 2020[ 31 ]; Sharma et al, 2020[ 33 ]; Tillett et al, 2020[ 35 ]; To et al, 2020[ 36 ]; Torres et al, 2021[ 37 ]) presents case reports of SARS-CoV-2 reinfection in different countries. In general, it appears that the RT-qPCR tests are used to diagnose different moments in the course of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…1) (References in Table 1: Abdallah et al, 2020[ 1 ]; AlFehaidi et al, 2020[ 2 ]; Amoozgar et al, 2020[ 5 ]; Bonifácio et. al., 2020[ 9 ]; Chan et al, 2020[ 10 ]; Duggan et al, 2021[ 13 ]; Fernandes Valente Takeda et al, 2020[ 14 ]; Hanif et al, 2020[ 17 ]; He et al, 2021[ 18 ]; Lafaie et al, 2020[ 20 ]; Lancman et al, 2020[ 22 ]; Mulder et al, 2020[ 24 ]; Nachmias et al, 2020[ 25 ]; Selvaraj et al, 2020[ 31 ]; Sharma et al, 2020[ 33 ]; Tillett et al, 2020[ 35 ]; To et al, 2020[ 36 ]; Torres et al, 2021[ 37 ]) presents case reports of SARS-CoV-2 reinfection in different countries. In general, it appears that the RT-qPCR tests are used to diagnose different moments in the course of the disease.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, symptomatic people have a high probability to "recover" or to temporary lose the COVID-19 symptoms as reinfection and persistence are newly claimed [20,21]. For asymptomatic individuals, no clear conclusion can be drawn about their recovery potential [19,22]. Whether, they may continue to support the transmission of the virus with a high load still remain to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2019, an outbreak of an emerging disease (COVID- 19) due to a novel coronavirus, the SARS-CoV-2, began in Wuhan, China and quickly spread in a substantial number of countries [1,2]. The COVID-19 pandemic, as a major global health threat, was declared by the WHO on 11 March 2020 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A case study reports that a 57-year-old man with a confirmed but asymptomatic case of COVID developed a mild but symptomatic case of COVID about three months later. It is not clear whether this was reinfection from a communitybased source, viral reinfection, or a delayed immune response [49]. Cases of potential reinfection are rare but have been reported; there is no strong evidence with respect to whether a recovered COVID patient can become reinfected.…”
Section: Is Long Covid More Than One Syndrome?mentioning
confidence: 99%